Improving Access to Postassault Healthcare for College Students: Creating a Campus-Based Sexual Assault Nurse Examiner Program. Issue 1 (9th January 2023) - Campbell, Rebecca; Markowitz, Jenifer; Fedewa, Tana; Shareef, Sameerah; Fenton, Danielle; Southard, Kimmins
ABSTRACT: National prevalence data indicate that college students are at a high risk for sexual assault, but most institutions of higher education do not provide postassault medical forensic examinations as part of student-facing healthcare services. College sexual assault patients might have access to sexual assault nurse examiners (SANEs) in local hospitals, if they are available where they are attending school, but unfortunately, many student victims do not have options for postassault health services. Creating campus-based SANE programs could address this gap in services and increase access to healthcare. In this article, we describe how we created a free-standing, campus-based SANE program at Michigan State University. We worked with a multidisciplinary community advisory board to identify core guiding principles to inform stakeholder engagement, program location decisions, program policies, training protocols, staffing plans, and collaborative partnerships with other disciplines (e.g., advocacy, law enforcement, prosecution, forensic sciences). We discuss how we navigated opening the program in the midst of the global COVID-19 pandemic and share lessons learned for creating campus-based SANE programs.